Association between plasma irisin in pregnancy and postpartum glucose levels among Chinese women: A cohort study. Issue 9 (17th March 2021) - Tang, Nu; Chen, Yajun; Wu, Weijia; Pan, Wenting; Wang, Dongyu; Zhang, Jingshu; Tan, Kaiyun; Jing, Jin; Cai, Li
Abstract: Aims/Introduction: The association between plasma irisin and glucose levels in the general population is controversial, and few studies have longitudinally detected this correlation. We aimed to examine whether irisin in pregnancy was associated with postpartum glucose levels among Chinese women and explore the modifiable factors. Materials and Methods: We carried out a prospective cohort study in Guangzhou, China, during 2017 and 2018, and 453 pregnant women (20–28 weeks) were enrolled. Plasma irisin levels in pregnancy were tested. At 6–8 weeks after delivery, 93 women with gestational diabetes mellitus (GDM) underwent a 75‐g oral glucose tolerance test, and the other 360 women had a fasting blood glucose (FBG) test. Multivariable linear, quantile and logistic regressions were carried out. Results: The mean plasma irisin in mid‐pregnancy was 13.73 ng/mL. We observed a significantly negative association between mid‐pregnancy irisin and postpartum FBG ( β : −0.056 ± 0.024). However, quantile regression showed the association was only significant in high percentiles of FBG levels ( P 50 to P 95 ), and the magnitude showed an increasing trend. Higher baseline irisin was also associated with a lower risk of postpartum impaired fasting glucose (relative risk 0.563, 95% confidence interval 0.384–0.825). Furthermore, we found significant interactions between irisin and predominant breast‐feeding on FBG and impaired fasting glucose (both P interaction  < 0.05). In women with GDM, baseline irisin was non‐significantly associated with postpartum postprandial 2‐h glucose levels ( β : −0.305 ± 0.160, P  = 0.061). Conclusions: Plasma irisin levels in mid‐pregnancy were negatively associated with FBG levels and impaired fasting glucose at 6–8 weeks postpartum among Chinese women, and stronger associations were observed in women with higher FBG values. Furthermore, breast‐feeding might modify this relationship. Abstract : The present study suggested that plasma irisin levels in mid‐pregnancy were negatively associated with FBG and IFG at 6‐8 weeks postpartum among Chinese women, and stronger associations were observed in women with higher FBG values. Moreover, breast‐feeding may modify this relationship. The results implied that irisin may play a protective role on glucose levels in postpartum women, especially in women with impaired glucose levels.